National questionnaire survey on what influences doctors' decisions about admission to intensive care - Escher, Monica (BMJ Publishing Group Ltd., 2004)
Objective To determine what influences doctors' decisions about admission of patients to intensive care. Design National questionnaire survey using eight clinical vignettes involving hypothetical patients. Setting Switzerland. Participants 402 Swiss doctors specialising in intensive care. Main outcome measures Rating of factors influencing decisions on admission and response to eight hypothetical clinical scenarios. Results Of 381 doctors agreeing to participate, 232 (61%) returned questionnaires. Most rated as important or very important the prognosis of the underlying disease (82%) and of the acute illness (81%) and the patients' wishes (71%). Few considered important the socioeconomic circumstances of the patient (2%), religious beliefs (3%), and emotional state (6%). In the vignettes, underlying disease (cancer versus non-cancerous disease) was not associated with admission to intensive care, but four other factors were: patients' wishes (odds ratio 3.0, 95% confidence interval 2.0 to 4.6), “upbeat” personality (2.9, 1.9 to 4.4), younger age (1.5, 1.1 to 2.2), and a greater number of beds available in intensive care (1.8, 1.2 to 2.5). Conclusions Doctors' decisions to admit patients to intensive care are influenced by patients' wishes and ethically problematic non-medical factors such as a patient's personality or availability of beds. Patients with cancer are not discriminated against.